The Relation Of Islamic And Local Wisdom: The Wearing Of Dinglo-Bengle Bracelet In The Village Of Sisir, Temanggung - I Idam Silmi (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2020)
This research was conducted in response to the various views of local community regarding the wearing of dinglo-bengle brecelets. The purpose of this research is; (1) to find out the relationship between Islam and the use of dinglo-bengle bracelets in the village of Sisir. (2) to envistigate the values of local wisdom in regard to the wearing of dinglo-bengle bracelets in the village of Sisir. The qualitative approach is used as developed by Craswell. Data analysis is based on the primary and secondary data where the interviews was conducted by purposing sampling techniques and direct observation in the field. Secondary data was obtained through the exploration of journals, research reports and relevant library sources. To ensure the validity of data, the researcher used data triangulation which included source and technique triangulation. The study found that (1) the community believe that the tradition of dinglo-bengle bracelets is an expression of socio-religious preference. (2) The wearing of dinglo-bengle bracelet reflects the values of local wisdom, such as spiritual values, moral values, educational values, cultural values, health values, and peace values.. Penelitian ini dilatarbelakangi oleh perbedaan pandangan masyarakat mengenai penggunaan gelang dinglo-bengle. Tujuan dari penelitian ini yaitu (1) Untuk mengetahui relasi Islam dengan penggunaan gelang dinglo-bengle di dusun Sisir. (2) Mengetahui nilai-nilai kearifan lokal yang terkandung dalam penggunaan gelang dinglo-bengle di dusun Sisir. Penelitian ini menggunakan pendekatan kualitatif seperti yang dikembangkan oleh Creswell. Analisis data dalam penelitian ini yaitu menggunakan data primer dan sekunder dengan wawancara yang menggunakan teknik purposive sampling dan observasi langsung di lapangan. Data sekundernya diperoleh melalui eksplorasi jurnal, laporan penelitian dan sumber pustaka yang releven. Untuk menguji keabsahan datanya peneliti menggunakan triangulsi data yang meliputi triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukan bahwa (1) pandangan masyarakat memaknai tradisi penggunaan gelang dinglo-bengle merupakan ungkapan refleksi sosial-keagamaan. (2) Penggunaan gelang dinglo-bengle memliki nilai- nilai kearifan lokal yang beragam seperti; nilai spiritual, nilai moral, nilai pendidikan, nilai kebudayaan, nilai kesehatan dan nilai kedamaian.